1994
DOI: 10.1093/oxfordjournals.aje.a117238
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Epidemiologic and Morbidity Effects of Routine Varicella Immunization of Preschool Children in the United States

Abstract: The authors studied the effects of routine varicella immunization of US preschool children and of implementation of a catch-up program in older children on the age distribution of cases and on overall morbidity, with emphasis on the sensitivity of the results to level of vaccine coverage, duration of protection, responsiveness to boosting, relative residual susceptibility and infectiousness, and degree of morbidity among vaccine breakthrough cases. An age-structured theoretical transmission model was used, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(96 citation statements)
references
References 0 publications
5
84
0
7
Order By: Relevance
“…The shape of the force of infection estimated for Canada and the United Kingdom (increasing in the pre-school years, peaking during primary school and declining thereafter) is consistent with other countries and with that of other childhood infections such as measles, mumps and rubella [40,41]. This suggests that preschool and school-age mixing is an important determinant of varicella transmission as with other childhood infections such as measles and rubella.…”
Section: Discussionsupporting
confidence: 71%
“…The shape of the force of infection estimated for Canada and the United Kingdom (increasing in the pre-school years, peaking during primary school and declining thereafter) is consistent with other countries and with that of other childhood infections such as measles, mumps and rubella [40,41]. This suggests that preschool and school-age mixing is an important determinant of varicella transmission as with other childhood infections such as measles and rubella.…”
Section: Discussionsupporting
confidence: 71%
“…6 The implementation of a childhood universal vaccination program has always been questioned due to a possible shift in the age distribution of varicella cases that would lead to increases in varicella incidence among adults and in overall morbidity. 7,8 In Spain, publicly funded varicella vaccination programmes were first introduced for the high-risk population in 1997; in 2005, the vaccine was included in the vaccination schedule for adolescents (age 11-14 y) who had not yet suffered from the illness. Currently, 2 of the 17 Autonomous Regions and the two Autonomous Cities (Ceuta and Melilla) of Spain have implemented varicella vaccination programmes for ages when most varicella cases can be prevented (age 12-15 mo).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the dynamic models 29,36,42,45,51,52 were based on the initial dynamic model developed by Halloran et al 54 , and the others 30,40,43,48 were based on similar approaches. All the dynamic models included the indirect effects of vaccination on non-vaccinated individuals (herd immunity) in the analysis.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Four studies used the rate reported by Halloran et al 54 , where 15% of the Table 2 Characteristics of indirect costs included in studies from society's perspective. successfully vaccinated individuals had lost their immunity by the end of life.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation